Diagnóstico, prognóstico e controle dos processos erosivos na Bacia do Córrego Guanabara, afluente do Rio Cabaçal - Costa, Jairo Ribeiro da (2015)
This research was conducted with the aim of applying the morphopedological approach and using techniques of geoprocessing that allowed to diagnose and subsidize the control of erosive processes, in the hydro graphic watershed of Guanabara stream, located between the geographic coordinated of latitudes 15° 02’ 44” and 15° 07’ 06” South and the longitudes 58° 25’ 31’’ and 58° 29’ 31” West of Greenwich, in the city of Reserva do Cabaçal/MT. The initial data were obtained by digital mean through the selected cartographic compilation, highlighting the most significant features as the interpretation and characterization of different forms of relief, erosive occurrence and use. It was used the geoprocessing software ArcGis 10.22 and satellite image SPOT 5 sensor HRG, MI 2150, passage of 2009, with spatial resolution of 2,5 meters and with support of Google Earth. In this phase of the research, it was implemented the first field activity, with general acknowledge and photographic takes, in which it was privileged the declivity and hydric functioning of waters of interflow and groundwater flow and the position and functioning of phreatic aquifer that constitutes fundamental mechanisms to the manifestation of these natural phenomenon of reproduction of erosive processes of ravines and gullies, that allowed determine the major environmental problems existent. Six morphopedological compartments were identifies and mapped, that resulted in two morphopedological maps, being one thematic and other in image, by maps of declivity and hypsometric, maps of occurrences and erosive susceptibility, in scale 1:30.000, beside the illustrated plank with pictures. This study revealed that the causes of linear erosive problems that occurred in the researched area, the ones with bigger size are situated in compartments CM – IV – small hills with Typic Quartzipisamment and CM-I- Hills with Typic Quartzipisamment, together present 47,1 of the total area researched, with a greater problem of the region due to the intense process of arsenisation that resulted in sandbank and silting of the water flow of Guanabara, followed by compartment CM-II – Undone escarpments with rocky outcrops. The compartment CM-VI – Hillside of engraved valleys in shape of “V” and CM-V – Medium hills with Cambisol present smaller index of erosive occurrences, they are 43,9% of this area, are favourable to the intensive Farming exploration only in theirs top portion. The diagnose and prognoses resulted in recommendation of measures of control and determined that the area of study presents itsef, in a greater part, unfavourable to the using intensive farming of lands.